Transferrin variation and evolution of Alaskan reindeer and caribou, Rangifer tarandus L. - Røed, Knut H.; Whitten, Ken R. (Rangifer, 1986)
Polyacrylamide gel electrophoresis was used to analyse transferrin variation in wild caribou (Rangifer tarandus granti) and domestic reindeer (R.t. tarandus) from Alaska. Eighteen alleles were detected in caribou and ten alleles were detected in reindeer. The most common allele was Tf 1 with a frequency of 0.304 and 0.408 in caribou and reindeer, respectively. The allele frequency distributions were significantly different in reindeer and caribou. This finding, together with the absence in reindeer of nine alleles present in caribou, suggests that little genetic exchange has taken place between caribou and reindeer in Alaska. The allele frequency distribution in Alaska caribou and reindeer are compared with those for other populations of caribou and reindeer. This comparison indicates that Alaskan caribou as well as Eurasian reindeer have evolved from a common ancesteral population different from the ancesteral population of Peary cairbou (R.t. pearyi) and Svalbard reindeer (R.t. platyrhynchus).